Vegetation of the Stjuža coastal lagoon in Strunjan landscape park (Slovenia) - Šajna, Nina (Annales. Series historia naturalis, 2005)
A draft history of the artificial Stjuža coastal lagoon was reconstructed on the basis of old maps (1804 and 1873); and compared with the present-day situation using GIS. The current data were simplified to obtain comparable caregories (landscape units) with old maps. The following major landscape units were distinguished: lagoon, salt marshes, mainland, brackish rivers and estuaries, ditches and canals, salt-pans, embankment, villages and roads. On current map, a total of 47 habitat types according to PHYSIS typology occurring in 206 polygons, which cover an area of 41.6 ha, were identified and described. Habitats with greater nature-conservancy value cover 26.7 ha of the total research area and constitute 40% of the polygons described. 55.6% of these belong to halophilous scrubs - Sarcocornetea fruticosi (= Arthrocnemetea fruticosi) - and 25.9% to annual salt pioneer sward communities, dominated by Salicornia europaea. Mediterranean salt swamps (Juncion maritimi) are present to a small extent only. It could be concluded that the artificial Stjuža lagoon, constructed for fish farming purposes, developed in habitat diverse coastal wetland area after partial abandonment.
Keywords: biogeografija; biogeography; laguna; mokrišča; Slovenia; Slovenija; Strunjan; vegetacija